Technological stress: psychophysiological aspects of working with modern information technology - Arnetz, Bengt B (Scandinavian Journal of Work, Environment & Health, 1997)
There is rapid technological transformation occurring in both work and social life. The results of information technology, such as mobile telephones, computers, and electronic networks, have been looked upon as the key to solving several of the most pressing problems of the Western world. At the same time, numerous studies have shown that the great majority of computerization projects fail to meet their deadlines with the originally specified functionality mainly because human factors are not sufficiently taken into account during the planning and implementation phase of the project. In a study of the bodily, mental, and psychophysiological reactions of employees involved in the design of advanced telecommunications systems and of office employees using regular video display technology, several stress-related psychosomatic disorders have been identified. They include sleep disturbances, psychophysiological stress and somatic complaints. Controlled intervention programs aimed at enhancing organizational structures and individual coping strategies have been proved effective in counteracting the negative effects of working with information technology. The two-way interaction between the external information technology environment and bodily and mental reactions needs to be taken more into account in the design and use of modern information technology. There appears to be an increased awareness of human aspects when the risks and benefits of the rapid spread of information technologies are discussed.
Keywords: computer; coping; psychophysiology; telecommunication; video display unit